(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Enhancing reading comprehension through short stories is a fundamental approach in educational pedagogy. This article presents diverse instructional methodologies while drawing insights from a study by Noor ul Ain et al. (2023) published in the Journal of Positive School Psychology. Their research showcased significant improvement in eleventh-year students’ reading skills at the secondary level in public schools in Rahim Yar Khan through the experimental use of short stories. By integrating these findings into broader instructional approaches, this article aims to offer educators a comprehensive guide to cultivate proficient reading comprehension skills through short story engagement.